EFFECT OF URSODEOXYCHOLIC ACID ON MATERNAL AND FETAL OUTCOME IN INTRAHEPATIC CHOLESTASIS OF PREGNANCY (The Research of Medical Science Review, 2025)
Background: Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific liver disorder associated with adverse maternal and fetal outcomes. Ursodeoxycholic acid (UDCA) is commonly used to manage ICP, but its effectiveness remains debated. Objective: This study evaluates the impact of UDCA on maternal and fetal outcomes in ICP patients.Methods: This prospective observational study was conducted at Shaikh Zayed Woman Hospital, Larkana, and Hashim Medical Center, Hyderabad, from January to December 2024. A total of 600 pregnant women (≥24 weeks’ gestation) diagnosed with ICP were included and assigned to either the UDCA group (n=300, receiving 15 mg/kg/day) or the conservative management group (n=300). Maternal outcomes, including pruritus severity (assessed via Visual Analog Scale) and liver function tests, were recorded at baseline and after 14 days of treatment. Obstetric complications and fetal outcomes, including gestational age at delivery, Apgar scores, and NICU admissions, were also analyzed. Data were compared using independent t-tests and chi-square tests, with p<0.05 considered statistically significant.Results: Pruritus relief was significantly higher in the UDCA group (85.3% vs. 41.7%, p<0.001). Serum bile acid levels, ALT, AST, and bilirubin significantly improved with UDCA. The UDCA group had lower preterm labor (10.3% vs. 22.7%, p=0.002) and postpartum hemorrhage rates (5.7% vs. 11.3%, p=0.021). Gestational age at delivery was higher (37.4 ± 1.6 vs. 35.9 ± 2.3 weeks, p<0.001), with fewer NICU admissions (9.0% vs. 20.3%, p<0.001) and stillbirths (1.3% vs. 4.7%, p=0.018) in the UDCA group.Conclusion: UDCA significantly improves maternal pruritus, liver function, and fetal outcomes in ICP patients, supporting its role in clinical management.